Kemampuan Berpikir Tingkat Tinggi Siswa SMP dalam Menyelesaikan Soal Matematika Model PISA - Megawati; Wardani, Ambarsari Kusuma; Hartatiana (Mathematics Education Journal, 2020)
This study aims to describe students' high-order thinking skills (HOTS) in solving PISA-like mathematics problem based on the indicators of evaluation ability. The research method used is qualitative research. Data collection techniques used were documentation, test, and interview. Results show that 30 students of junior high school Xaverius 1 Palembang who had completed the problem, there were 73% of students' thinking ability is still low, especially in evaluate. Indicators evaluate appear if students are able to analyze the problem appropriately, understand the intent of the question correctly, and provide the right reason/evidence. Based on the analysis of students’ answer and interview, it can be conclude that only 6% out of 30 students categorized well in evaluation stage when solving mathematics problem such as PISA.